How mathematics works - "Vorderman, Carol" (DK London, 1996)
A guide introducing the ways in which mathematics is working around us. Activities, designed for nine- to fourteen-year-olds, explain the major concepts of mathematics. The book aims to improve mental arithmetic, explain geometry and algebra, and introduce the theories of today's mathematicians